New Kid on the Block: The Efficacy of Phytomedicine Extracts Urox® in Reducing Overactive Bladder Symptoms in Rats - Zapała, Łukasz; Juszczak, Kajetan; Adamczyk, Przemysław; Adamowicz, Jan; Ślusarczyk, Aleksander; Kluz, Tomasz; Misiek, Marcin; Rogowski, Artur; Grzybowska, Magdalena Emilia; Stangel-Wójcikiewicz, Klaudia; Zaborowski, Mikołaj Piotr; Poleszak, Ewa; et al. (Frontiers in Molecular Biosciences, 2022)
The aim of the current study was to determine if phytomedicine (UROX®) would reverse retinyl acetate (RA)-induced changes characteristic of bladder overactivity. There were 60 rats divided into 4 following groups: I - control, II - received RA to induce detrusor overactivity (DO), III - received UROX (840 mg/daily for 14 days), and IV – received combination of RA and UROX. The cystometry was performed 2 days after the last dose of UROX®. Next, urothelium thickness, and biochemical parameters measurement were performed. In group IV, a decrease in basal pressure and detrusor overactivity index was noted when compared to group II. Furthermore, in group IV the following parameters were increased: threshold pressure, voided volume, intercontraction interval, and bladder compliance in comparison with group II. There were significant elevations in c-Fos expression in the neuronal voiding centers in group II, while the ex-pression of c-Fos in group IV was normalized. No significant changes in the values of the analyzed biomarkers in group III were found, while in group II an elevation of BDNF, NGF, CGRP, ATP, Rho kinase, malondialdehyde, 3-nitrotyrosine, TRPV1, OCT-3 and VAChT, then a decrease of E-cadherin and Z01. A successful restoration of all the above-mentioned biomarkers’ levels was observed in group IV. Phytomedicine extracts (UROX®) were found to be po-tent to reverse RA-induced changes in both several cystometric and biochemical parameters that are determinants of OAB. The actions of UROX® were proved to be dependent on several factors, including growth factors and several OAB biomarkers, but not pro-inflammatory cytokines.